Arctic Ocean Response to Greenland Sea Wind Anomalies in a Suite of Model Simulations - Muilwijk, Morven; Ilicak, Mehmet; Cornish, Sam B.; Danilov, Sergey; Gelderloos, Renske; Gerdes, Rüdiger; Haid, Verena; Haine, Thomas W. N.; Johnson, Helen L.; Kostov, Yavor; Kovács, Tamás; Lique, Camille; et al. (American Geophysical Union (AGU), 2019)
AbstractMultimodel Arctic Ocean “climate response function” experiments are analyzed in order to explore the effects of anomalous wind forcing over the Greenland Sea (GS) on poleward ocean heat transport, Atlantic Water (AW) pathways, and the extent of Arctic sea ice. Particular emphasis is placed on the sensitivity of the AW circulation to anomalously strong or weak GS winds in relation to natural variability, the latter manifested as part of the North Atlantic Oscillation. We find that anomalously strong (weak) GS wind forcing, comparable in strength to a strong positive (negative) North Atlantic Oscillation index, results in an intensification (weakening) of the poleward AW flow, extending from south of the North Atlantic Subpolar Gyre, through the Nordic Seas, and all the way into the Canadian Basin. Reconstructions made utilizing the calculated climate response functions explain ∼50% of the simulated AW flow variance; this is the proportion of variability that can be explained by GS wind forcing. In the Barents and Kara Seas, there is a clear relationship between the wind‐driven anomalous AW inflow and the sea ice extent. Most of the anomalous AW heat is lost to the atmosphere, and loss of sea ice in the Barents Sea results in even more heat loss to the atmosphere, and thus effective ocean cooling. Release of passive tracers in a subset of the suite of models reveals differences in circulation patterns and shows that the flow of AW in the Arctic Ocean is highly dependent on the wind stress in the Nordic Seas.
Keywords: wind forcing; Sea ice; Atlantic Water; Famos; [SDU.STU.OC] Sciences of the Universe [physics]/Earth Sciences/Oceanography; sea ice; [SDU] Sciences of the Universe [physics]; Wind forcing; model intercomparison; [SDU]Sciences of the Universe [physics]; Arctic Ocean; Model intercomparison; [SDU.STU.OC]Sciences of the Universe [physics]/Earth Sciences/Oceanography